Past and future roles of paired watersheds: a North American inventory and anecdotes from the Caspar Creek Experimental Watersheds - Richardson, Paul W.; Cafferata, Peter H.; Dymond, Salli F.; Keppeler, Elizabeth T.; Wagenbrenner, Joseph W.; Whiting, John A. (Frontiers in Forests and Global Change, 2023)
Given the high costs of constructing, maintaining, monitoring, and sampling paired watersheds, it is prudent to ask “Are paired watershed studies still worth the effort?” We present a compilation of 90 North American paired watershed studies and use examples from the Caspar Creek Experimental Watersheds to contend that paired watershed studies are still worth the effort and will continue to remain relevant in an era of big data and short funding cycles. We offer three reasons to justify this assertion. First, paired watersheds allow for watershed-scale experiments that have produced insights into hydrologic processes, water quality, and nutrient cycling for over 100 years. Paired watersheds remain an important guide to inform best management practices for timber harvesting and other land-management concerns. Second, paired watersheds can produce long climate, streamflow, and water quality records because sites are frequently maintained over the course of multiple experiments or long post-treatment periods. Long-term datasets can reveal ecological surprises, such as changes in climate-streamflow relationships driven by slow successional processes. Having multiple watershed records helps identify the cause of these changes. Third, paired watersheds produce data that are ideal for developing and testing hydrologic models. Ultimately, the fate of paired watersheds is up to the scientific community and funding agencies. We hope that their importance continues to be recognized.